THE INFLUENCE OF ATMOSPHERE, ONLINE REVIEWS AND CUSTOMER VALUE ON REPURCHASE INTENTION - Dwini, Sekar; Tuti, Meylani (Institut Bisnis Nusantara, 2024)
This study aims to determine the effect of atmosphere, online review and customer value on repurchase intention at Kina Cafe & Bar. The sampling technique used is accidental sampling with a total of 250 respondents. Data analysis method using SEM (Structural Equation Model) with SmartPLS software. The research results show that the atmosphere at Kina Cafe & Bar does not have a significant influence on repurchase intentions, indicating that the atmospheric elements at Kina Cafe & Bar are not the main factors influencing customers' decisions to shop there again. In contrast, online reviews have a significant influence on repurchase intentions indicating that customers' online reviews can be an important component in determining customers' repurchase intentions. Apart from that, consumer values are also proven to have a big influence on the desire to repurchase. This shows that consumers who feel they get good value from goods or services at Kina Cafe & Bar are more likely to buy again. In this way, Kina Cafe & Bar management can concentrate on continuing to sell goods and services.